Acute-onset psychosis induced by a therapeutic dose of parenteral hyoscine butylbromide: A case report - Emorinken, Airenakho; Akpasubi, Blessyn Omoye; Izirein, Hannah Olohirere; Oyerinde, Adeola (Indian Journal of Case Reports, 2024)
Anticholinergic medications are frequently prescribed for gastrointestinal and genitourinary spasms. Psychosis, when present, results from anticholinergic overdose or toxicity. In the literature, anticholinergic-induced psychosis at therapeutic doses in patients with normal cognition is extremely uncommon. Here, we describe the case of a 28-year-old female who presented with auditory and visual hallucinations, stereotypy, and agitation after receiving a single intramuscular injection of 20 mg hyoscine butylbromide for dysmenorrhea. Even though it is rare for a therapeutic dose of hyoscine butylbromide to cause psychosis, clinicians should maintain a high index of suspicion and be cautious when administering or prescribing anticholinergics.